2011
DOI: 10.1016/j.ufug.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Predicting urban forest growth and its impact on residential landscape water demand in a semiarid urban environment

Abstract: a b s t r a c tWe present an innovative approach to estimating residential irrigation water demand for a large metropolitan area using GIS data, weather station data, and a water budget modeling approach commonly used by plant scientists and landscape management professionals. An important question addressed by our study is how a growing urban forest affects the overall irrigation water demand of a semiarid metropolitan area. To estimate the amount of water required by residential landscaping, we consider wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…tree/shrub or turf grass), the water-loss rate for different landscaping types, the efficiency with which the landscape is irrigated, and local climatic factors (i.e. reference evapotranspiration and precipitation) (Lowry et al 2011). No study has been conducted to quantify this but going by the high amounts of domestic and municipal water consumption it can be assumed that most of this goes towards watering plants and lawn.…”
Section: Water Consumption By Sectormentioning
confidence: 99%
“…tree/shrub or turf grass), the water-loss rate for different landscaping types, the efficiency with which the landscape is irrigated, and local climatic factors (i.e. reference evapotranspiration and precipitation) (Lowry et al 2011). No study has been conducted to quantify this but going by the high amounts of domestic and municipal water consumption it can be assumed that most of this goes towards watering plants and lawn.…”
Section: Water Consumption By Sectormentioning
confidence: 99%
“…There are similar studies that focus on urban forest growth and its impact on the water demand of residential landscapes, conducted by Lowry, Ramsey, and Kjelgren (2011), water demand in the outdoor areas in the neighbourhoods of Salt Lake County (USA) was analysed. Studies of this type are not often conducted in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…While we recognize that block scale population density is not the only attribute describing urban form that is related to tree canopy cover, several studies have shown evidence of a decay in tree cover as population density increases [ 35 , 37 , 63 , 64 ]. Population density is also an easily accessible metric at broad spatial scales that is both correlated with and related to other aspects of urban form such as building type, compactness, and average block size [ 65 ], and some of these factors have also been shown to be related to tree cover [ 35 , 36 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…First, tree cover is also associated with other factors, including differences in climate, biome, neighborhood age, urban density, the intensity of urban settlement, and other aspects of urban form [34][35][36][37][38][39][40]. In some studies, covariates such as terrain, housing type and density explained part of the variation between tree cover and socio-economic variables [25,29,39,41,42]. Furthermore, socio-economic variables are themselves also correlated with aspects of urban form, such as the degree of sprawl and population density [43,44].…”
Section: Introductionmentioning
confidence: 99%